Impact of the Crane Collapse on the South Sumatra LRT Construction Project on the Environment and the Company - Fauzan Wanuri; Fazlurrahman Mujiharyadi; Nugroho Eko Karyatno (Penerbit Jurnal Indonesia, 2024)
This report examines the crane collapse incident during the Light Rail Transit (LRT) construction project in Palembang, South Sumatra. This case study analyzes the impact of the event on the environment and the company, and evaluates the incident handling from the perspective of engineering ethics and code of conduct. The methodology used includes field observations, interviews, and data analysis from investigation reports. The discussion covers aspects of occupational safety, health, and environment (SHE), as well as professionalism in engineering. The report also highlights the importance of risk management, geotechnical analysis, and innovation in construction techniques. The conclusions drawn emphasize the priority of workplace safety, the importance of comprehensive risk analysis, and adherence to engineering professional ethics. Recommendations include improving safety standards, stricter supervision, and thorough risk evaluation in similar infrastructure projects in the future. A key lesson from this incident is the importance of balancing technological advancement with safety in infrastructure development.